1989
DOI: 10.1523/jneurosci.09-05-01705.1989
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal damage associated with prolonged and fatal stress in primates

Abstract: Sustained exposure to glucocorticoids (GCs), adrenal hormones secreted during stress, can cause neural degeneration in the rat. This is particularly so in the hippocampus, a principal neural target site for GCs, in which GCs can exacerbate the rate of neuron death during normal aging, as well as the severity of neuronal damage after various neurological insults. Thus, stress can be a potent modulator of hippocampal degeneration in the rat. The present report suggests a similar association in the primate. Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
280
3
12

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 672 publications
(305 citation statements)
references
References 23 publications
10
280
3
12
Order By: Relevance
“…Sex differences in brain structures and mechanisms occur in other brain regions besides hypothalamus, such as hippocampus, and they appear to be involved in aspects of cognitive function and other processes that go beyond the reproductive process itself, such as the higher incidence of depression in women and of substance abuse in men (122). There are also sex differences in the severity of brain damage resulting from transient ischemia (49) and sex differences in the response of the brain to lesions (104) and to severe, chronic stress (100,141). A recent study has shown that the stress-induced atrophy of apical dendrites of CA3 pyramidal neurons occurs in male rats but not in female rats (42).…”
Section: Importance Of Sex Differences and Sex Hormonesmentioning
confidence: 99%
“…Sex differences in brain structures and mechanisms occur in other brain regions besides hypothalamus, such as hippocampus, and they appear to be involved in aspects of cognitive function and other processes that go beyond the reproductive process itself, such as the higher incidence of depression in women and of substance abuse in men (122). There are also sex differences in the severity of brain damage resulting from transient ischemia (49) and sex differences in the response of the brain to lesions (104) and to severe, chronic stress (100,141). A recent study has shown that the stress-induced atrophy of apical dendrites of CA3 pyramidal neurons occurs in male rats but not in female rats (42).…”
Section: Importance Of Sex Differences and Sex Hormonesmentioning
confidence: 99%
“…A number of studies have found evidence of neuronal atrophy and loss of hippocampal neurons in response to stress (Magarinos et al 1996;Uno et al 1989;Sapolsky et al 1985), and a report of reduced hippocampal volumes in elderly patients with histories of depression suggests that analogous processes may occur in individuals with depression (Sheline et al 1996). Some models of mood disorders (Hyman and Nestler 1996; Post 1992) have attempted to incorporate the notion of compensatory processes into an understanding of the pathophysiologic changes that occur in patients with mood disorders, but few studies have tested these notions empirically (Post 1992).…”
Section: Regulation Of Er Stress Proteins Such As the 78-kilodalton mentioning
confidence: 99%
“…Up until now, most studies showed that major depression is associated with a selective volume loss of hippocampus (Sheline et al, 1996;Bremner et al, 2000;Frodl et al, 2002), whereas one post-mortem study reported no effect of major depression or glucocorticoid treatment on the hippocampus (Muller et al, 2001). Besides cell loss induced by prolonged stress and glucocorticoid exposure (Uno et al, 1989;Sapolsky et al, 1990), another possibility underlying the decreased hippocampal volume is that chronic stress induces apical dendrite atrophy of CA3 pyramidal neurons, which is mediated by activation of endogenous excitatory amino acids (EAAs, eg glutamate) because the interference with the action of EAAs could prevent the atrophy (Watanabe et al, 1992;Magarinos et al, 1996). This result is consistent with the evidence that stress induces EAAsmediated excitatory input to the hippocampal CA3 (Krugers et al, 1993;Bartanusz et al, 1995).…”
Section: Introductionmentioning
confidence: 99%